2019
DOI: 10.3390/genes10100831
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Mating in Pathogenic Fungi—A Plastic Trait

Abstract: The impact of fungi on human and plant health is an ever-increasing issue. Recent studies have estimated that human fungal infections result in an excess of one million deaths per year and plant fungal infections resulting in the loss of crop yields worth approximately 200 million per annum. Sexual reproduction in these economically important fungi has evolved in response to the environmental stresses encountered by the pathogens as a method to target DNA damage. Meiosis is integral to this process, through in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…The unusual cryptic nature of these sexual cycles led to clonal populations that might be limited in recombination events, thus having broad implications for the evolution of eukaryotic microbial pathogens. The apparent functionality of the mating type genes has been observed in species without known sexual structures, suggesting the occurrence of at least some degree of recombination (Usher, 2019). In line with sporulation ability, Zhao et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The unusual cryptic nature of these sexual cycles led to clonal populations that might be limited in recombination events, thus having broad implications for the evolution of eukaryotic microbial pathogens. The apparent functionality of the mating type genes has been observed in species without known sexual structures, suggesting the occurrence of at least some degree of recombination (Usher, 2019). In line with sporulation ability, Zhao et al.…”
Section: Resultsmentioning
confidence: 99%
“…The unusual cryptic nature of these sexual cycles led to clonal populations that might be limited in recombination events, thus having broad implications for the evolution of eukaryotic microbial pathogens. The apparent functionality of the mating type genes has been observed in species without known sexual structures, suggesting the occurrence of at least some degree of recombination (Usher, 2019). In line with sporulation ability, Zhao et al (2019) found that monoacylglycerol lipase is involved on arachidonic acid production, a compound that is required for conidia formation and pseudothecial development in S. eturmiunum, an opportunistic plant pathogen causing blight in onion.…”
Section: Genomes Of Cidefi 212 213 and 216mentioning
confidence: 90%
“…Nevertheless, in all organisms, the process requires two characteristics: specificity of the interaction and a long enough contact time to ensure cellular fusion and/or gene transfer. Because mating systems are both complex and fastevolving [9][10][11][12][13][14], there are a wide variety of strategies to achieve these characteristics.…”
Section: Mating Systems: Short Overviewmentioning
confidence: 99%
“…The C. albicans genome retained many mating-related homologs, but some key meiosis regulators were conspicuously absent, such as IME1 (master regulator of meiosis initiation in S. cerevisiae ) and SPO13 (regulator of segregation during meiosis I in S. cerevisiae ). Subsequent studies identified the presence of several previously overlooked ‘meiosis-specific’ genes in C. albicans although the involvement of most homologs in the parasexual cycle remains unstudied [reviewed in ( Sherwood and Bennett, 2009 ; Usher, 2019 )].…”
Section: Parasexual Ploidy Reduction Promotes Genetic Diversitymentioning
confidence: 99%